Exploring Affective Experiences of Lower-Secondary Students in Arabic Writing (Kitabah): A Case Study at SMP Muhammadiyah 5 Ngawi - Muhammad An Naufar Prastyo; Yeni Maratus Solekah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This qualitative phenomenological study explores affective experiences of lower-secondary students during Arabic writing (kitabah) learning, identifying triggers of positive and negative emotions and mapping how emotional dynamics shape motivation and learning outcomes. Data collection techniques proposed for field implementation include in-depth interviews with students, analysis of post-lesson reflection journals, and non-participant classroom observations. Synthesis across Arabic education studies highlights that enjoyment, pride, and confidence emerge when tasks are scaffolded, feedback is supportive, and peer collaboration is active, whereas anxiety, frustration, and shame arise from grammatical load, unfamiliar script conventions, monotonous teaching, and low self-efficacy. Emotional states modulate effort, persistence, and performance: reduced anxiety and enhanced self-efficacy correlate with higher engagement and better writing quality, while persistent anxiety depresses attention and recall, undermining outcomes. The study formulates a practical framework integrating supportive climate, iterative practice, multimodal media, and reflective routines to regulate emotion, sustain motivation, and improve kitabah performance. Implications inform teachers, curriculum designers, and school leaders seeking evidence-based, emotionally attuned Arabic writing pedagogy at the junior secondary level.